2015
DOI: 10.5114/pjp.2015.57249
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of indoleamine-2,3-dioxygenase and the receptors for transforming growth factor β and interferon γ in metastatic lymph nodes in malignant melanoma

Abstract: We analyzed the prognostic significance of indoleamine-2,3-dioxygenase (IDO) and type 1 receptors for transforming growth factor beta (TGF-βR1) and interferon gamma (IFN-γR1) in resected nodal metastases of 48 malignant melanoma patients. In 32 cases the corresponding skin tumors were available. We used immunohistochemical (IHC) staining which was assessed by pathologists and by a computer-aided algorithm that yielded quantitative results, both absolute and relative. We correlated the results with the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…This study demonstrates that IDO activity at baseline is an important prognostic marker for patients with NSCLC treated with fractionated RT. This is in agreement with previous studies that baseline IDO immune status plays a prognostic role after surgery or chemotherapy (16,17,20-22). Our data demonstrated low activity of IDO, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrates that IDO activity at baseline is an important prognostic marker for patients with NSCLC treated with fractionated RT. This is in agreement with previous studies that baseline IDO immune status plays a prognostic role after surgery or chemotherapy (16,17,20-22). Our data demonstrated low activity of IDO, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Rubel et al found that high amounts of both IDO+ melanoma and stromal cells correlate with poor progression-free survival (PFS), and high amounts of IDO+ melanoma cells were also positively associated with Breslow’s depth [ 13 ]. In another study, abundance of IDO-expressing melanoma cells in LNMs of CM was associated with poor OS [ 14 ]. Similarly, our results indicate that IDO expression in both stromal immune cells and tumor cells promote tumorigenesis in CM, as the number of both IDO+ stromal immune cells and IDO+ tumor cells was significantly higher in malignant compared with benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of IDO have been reported in melanoma (Brody et al, 2009), PDA (Witkiewicz et al, 2009) and ovarian cancer (Inaba et al, 2009) as well as many other tumors (Wainwright et al, 2012). IDO is associated with reduced CD8 T cell infiltration and poor patient survival (Pelak et al, 2015; Speeckaert et al, 2012). IDO promotes peritoneal dissemination of ovarian cancer cells by promoting angiogenesis and generating a tolerogenic environment that suppresses anti-tumor immune responses by NK cells and T cells (Tanizaki et al, 2014; Wang et al, 2012).…”
Section: Metabolic Challenges In the Tme: Impact On T Lymphocytes Andmentioning
confidence: 99%